Sediment Transport Study In Estuary Of Weriagar River, Kabupaten Teluk Bintuni, West Papua - Fera Dwi Setyani (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2020)
Sediment transport study can be done by 3D numerical modeling for hydrodynamic and sediment transport simulation. In this study, 3D numerical modeling is calibrated by observation data, such as surface elevation and current speed. Hydrodynamic and sediment transport in estuary of Weriagar River is simulated for 31 days. Hydrodynamic simulation result shows that hydrodynamic in Weriagar River is dominated by river discharge while tide dominates the hydrodynamic in the estuary. Current speed is increasing during spring tide but current flows faster during ebb because the river discharge also flows to the estuary. Vertical profile indicates that current speed decreases as the elevation gets deeper. This condition is caused by bed resistance near the bed. Sediment transport simulation result shows bed level changes in Weriagar River. Maximum erosion occurs about 20 cm near the river bend with bed level change rate 0,02 m/day. Maximum erosion occurs in this location because the flow pattern and current speed increases at ebb condition. At the estuary, the erosion occurs with small intensity. This happens because longshore current from sea is entering the river mouth but is blocked by more dominate river discharge. Current speed affects suspended sediment concentration and bed level change rate